Persian Version of Healthy Lifestyle and Personal Control Questionnaire (HLPCQ): A Confirmatory Factor Analysis - Darijani, Zahra; Ahmadipour, Habibeh (Journal of Preventive Medicine And Care, 2018)
Background: lifestyle modification is known as the cornerstone for prevention and treatment of chronic diseases. To promote individual’s lifestyle, the first step is to measure their lifestyle by a valid and reliable tool. The aim of present study was to evaluate psychometric properties of the Persian version of Healthy Lifestyle and Personal Control Questionnaire (HLPCQ). Method: A crosssectional study carried out on 300 medical students in Kerman University of Medical Sciences, Iran. Data collected using a questionnaire contained demographic data and Persian version of HLPCQ. The reliability of the questionnaire determined using Cronbach’s alpha and intra class correlation coefficient (ICC). The construct validity of the questionnaire evaluated by exploratory and confirmatory factor analysis. Data were analyzed by SPSS version 19 and Lisrel 8.8. Results: Internal consistency of HLPCQ was 0.78 using Cronbach’s alpha and 0.80 by ICC. In confirmatory factor analysis, the scale had acceptable goodness of fit indices. Conclusions: The Persian version of HLPCQ had excellent psychometric properties and can be used in in primary health care settings.
Keywords: Life style; reliability; validity; questionnaire; Iran